Field Experience Report: U.S. Department of Health and Human Services, Office of Disease Prevention and Health Promotion - Stephen, Mellina (My University, 2011)
In accordance with requirements for the Masters of Public Health degree, I completed my field experience with the U.S. Department of Health and Human Services’ Office of Disease Prevention and Health Promotion (ODPHP) in the Fall of 2011. ODPHP is a policy office whose work involves collaborating and coordinating with various federal and nonfederal agencies in support of programming, information dissemination, et cetera related to national initiatives. ODPHP’s major undertakings include developing the 2010 Dietary Guidelines for Americans, the 2008 Physical Activity Guidelines for Americans, and Healthy People 2010 & 2020. ODPHP is housed within the Office of Public Health and Science under the Assistant Secretary for Health. The primary focus for my experience was to assist members of the Prevention Science Team in fulfillment of team projects and activities, as a Visiting Prevention Scholar. As a member of the science team, I made several contributions including developing a physical activity consumer brochure to be used in addition to an existing Dietary Guidelines brochure. My experience at ODPHP has given me valuable insight into the process of how a government agency supports, advises, and provides leadership to its federal and nonfederal partners in the advancement of mandated programs and policies.
Keywords: ODPHP; Nutritional Initiatives; HHS; Health Policy; Public Health (0573)